Long Term Evolution 4G and Beyond - Paradisi, Alberto; Yacoub, Michel Daoud; Lira Figueiredo, Fabrício; Tronco, Tania (Telecommunications and Information Technology,, 2016)
This book focus on Long Term Evolution (LTE) and beyond. The chapters describe different aspects of research and development in LTE, LTE-Advanced (4G systems) and LTE-450 MHz such as telecommunications regulatory framework, voice over LTE, link adaptation, power control, interference mitigation mechanisms, performance evaluation for different types of antennas, cognitive mesh network, integration of LTE network and satellite, test environment, power amplifiers and so on. It is useful for researchers in the field of mobile communications.